2012
DOI: 10.1016/j.jcrs.2012.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Intrastromal corneal ring segments: Effect of relationship between alignment and topographic keratometric meridians

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…Tu et al (2012) reported greater but non-significant reduction in refractive errors and keratometric astigmatism for incisions on the flat meridian compared to those performed on the steep meridian or oblique sites. 24 Although there is no general agreement on a particular reference site, in most studies, the steepest corneal meridian was used as an optimal location. 40 The location used in the current study was on the steepest topographic meridian.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tu et al (2012) reported greater but non-significant reduction in refractive errors and keratometric astigmatism for incisions on the flat meridian compared to those performed on the steep meridian or oblique sites. 24 Although there is no general agreement on a particular reference site, in most studies, the steepest corneal meridian was used as an optimal location. 40 The location used in the current study was on the steepest topographic meridian.…”
Section: Discussionmentioning
confidence: 99%
“…20 In order to obtain the optimal clinical outcomes after the ICRS implantation, each manufacture provides a specific nomogram to help clinicians select the best ring characteristics according to clinical data. The available nomograms A c c e p t e d M a n u s c r i p t 5 were mainly developed based on the distribution of ectatic corneal region, its symmetry status, and the spherical/cylindrical components of refractive error, while other factors such as preoperative visual acuity, 9 mean keratometry, corneal topographic pattern, 21 keratoconus grading, 15,22,23 aberrations, 10 coincidence between refractive, topographic and comatic axes, 24,25 incision location, 24,26 corneal biomechanical properties, 22,27,28 and internal astigmatism 15 may affect the surgical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Segments 6 mm in diameter decreased the corneal astigmatism by 1.54 D at 99° from the preoperative steep meridian. Vectorial analysis of ICRS implantation was performed in a few studies [ 7 , 8 ]. Our results agreed with an earlier study in that the corneal astigmatism decreased after vector analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results agreed with an earlier study in that the corneal astigmatism decreased after vector analysis. Meanwhile, reports by Tu et al [ 7 , 8 ] indicated that the maximum reduction in astigmatism (–2.67 D) occurred when the incision was placed in the flat meridian (perpendicular group) and the least effect (–0.65 D) was when the incision was placed in the steep meridian (meridional group). The differences in study design and analysis make it difficult to directly compare these previous results with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation